Teacher reward challenges and student academic performance in selected secondary schools in Luwero district. - Auk, Timothy; Sekiwu, Denis; Edoru, John Michael (International Journal of Research in Education Humanities and Commerce, 2025)
Poor academic performance remains a major challenge in Luwero District, mainly attributed to a disproportionality in teacher reward systems. Thus, this study was intended to explore how teacher reward challenges, affect student academic performance in selected secondary schools in Luwero District. Using the descriptive research design, data was collected from a sample of 108 participants. The findings were that the teachers and administrators enrolled, showed that teacher reward challenges like meager payment 77.3%, rewards not on merit 63.9%, no recognition 66.0%, inadequate funding for teachers reward 85.6, poor management of teacher reward systems 76.3% and salary delay 84.5% influences student academic performance. The current teacher reward systems may indicate that these challenges continues to have a significant impact on student academic performance. Interventions targeting teacher reward systems, particularly on monetary and non-monetary reward, non-delayed salaries, no meager payment, recognition aspects, are vital.